If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-25=-(-8x-6)-3x+36
We move all terms to the left:
-25-(-(-8x-6)-3x+36)=0
We calculate terms in parentheses: -(-(-8x-6)-3x+36), so:We get rid of parentheses
-(-8x-6)-3x+36
We add all the numbers together, and all the variables
-3x-(-8x-6)+36
We get rid of parentheses
-3x+8x+6+36
We add all the numbers together, and all the variables
5x+42
Back to the equation:
-(5x+42)
-5x-42-25=0
We add all the numbers together, and all the variables
-5x-67=0
We move all terms containing x to the left, all other terms to the right
-5x=67
x=67/-5
x=-13+2/5
| x+10+x+10=3x | | y-0.75y=1100 | | -a/17=-1/17 | | 24.5+a=26.5 | | 9x-21+1=67 | | 99-a=66 | | 3/4=(-(x+11))/(4x)+1/(2x) | | 2(5-y)=5(y-5 | | 3(x-8)=+4 | | 6.2/18.6=4.5/x | | 3-10(x+4)=-(-5x+7) | | 11x+2(-4x+3)=-3(-2x+9) | | -4(5x-6)=6(-3x+8) | | -4(5x-6)=6×(-3x+8) | | 10x–3x=77 | | 8x-15-3x=-(4x-30) | | 3=7x+14 | | 7x+18=5x-22 | | X+2y=1900 | | 12x+4+3x=13x+18 | | 8x+7=6x-12 | | x/5+2x=9 | | 2x-5=x+18= | | 2(14+x)=37+x | | 3(x+4)=x+18= | | 8(2x+3)=24 | | x+10=2(x-1) | | x(x+8)=768 | | 7-(5x+-13)=-25 | | 4n+8=-8+6n | | -17w-7+2=17w-5 | | (2x-1)+(3x-3)+(9x-9)=1 |